Exploring the Intricacies of Lexicology: A Comprehensive Study of Vocabulary, Word Relationships, and Language Evolution (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Lexicology, a crucial field in linguistics, delves into the vocabulary and characteristics of words, word-groups, and their development within a language. This study classifies lexicology into general, special, descriptive, historical, and comparative types, each shedding light on distinct aspects of language analysis. By exploring the relationship between lexicology and grammar, phonetics, language history, and stylistics, this research underscores the interconnected nature of language studies. Moreover, the interaction between phonetics and word meaning, the impact of language history on semantic evolution, and the junction of lexicology with stylistics contribute to a comprehensive understanding of linguistic structures. The thesis navigates through syntagmatic and paradigmatic word relationships, emphasizing the contextual and inter-vocabulary connections that shape language usage.